Does size or age of innovative firms affect their growth persistence? -Evidence from a panel of innovative Spanish firms- - Daria Ciriaci; Pietro Moncada-Paternò-Castello; Peter Voigt (European Commission, Joint Research Centre (JRC), 2012)
This study examines serial correlation in employment, sales and innovative sales growth rates in a balanced panel of 3,300 Spanish firms over the years 2002-2009, obtained by matching different waves of the Spanish Encuesta sobre Innovacion en las Empresas, the Spanish innovation survey conducted annually by the Spanish National Statistics Institute (INE). The main objective is to verify whether the changes (increase/decrease) in these figures are persistent over time, whether such persistence (if any) differs between SMEs and larger firms, and if it is affected by a firm's age. To do so, we adopted a semi-parametric quantile regression approach. This methodology is well suited to cases where outliers (high-growth firms) are the subject of investigation and/or when they have to be assumed as being very heterogeneous. Empirical results indicate that among those innovative firms experiencing high employment growth, the smaller and younger grow faster than larger firms, but the jobs they create are not persistent over time. However, while being smaller and younger helps growing more in terms of employment and sales, it is not an advantage when innovative sales growth is considered: in this case larger firms experience faster growth.
Keywords: L11; L25; 330; Serial correlation; quantile regression model; Spanish firms; firm size; firm age; job creation; fast growing firms